Nurturing Political Engagement: Political Communication Strategies for Generation Z in the Lead-up to the 2024 Election in West Java - Dewi, Evie Ariadne Shinta; Arifin, Hadi S; Fuadi, Ikhsan (The Journal of Society and Media, 2023)
President Joko Widodo stated that in 2045, Generation Z (gen-Z) will change the face of Indonesian politics. The demographics of Generation Z in significant numbers will influence the direction of Indonesian politics due to their ability to control election votes. Gen-Z, which has grown up with the development of technology and is vulnerable to the impact of misinformation, disinformation, and misinformation, must be strengthened through political education. For this goal, parties and KPU need to devise new strategies for younger generations. Data was collected from political party leaders and KPU commissioners in West Java through questionnaires and in-depth interviews. The results show that Gen-Z West Java is an active social media user, the time spent every day is on average above four hours (46.2%), with the choice of the top four platforms, WhatsApp (94.2%), Instagram (89.7%), Youtube (69.9%), Tiktok (66.7%) and Facebook (44.8%). Gen-Z prefers research, podcasts, memes, and political humor for political communication. However, regional KPU staff and political parties struggle to meet their needs for voter education mediaApproximately 80% of Gen-Z in West Java plan to vote in the 2024 elections. KPU and political parties need skilled Content Creators to engage Gen-Z and encourage their participation in elections.